ANALISIS PENDAPATAN USAHATANI LADA HITAM DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA DI KECAMATAN MELINTING KABUPATEN LAMPUNG TIMUR - Apriliana, Bella; Endaryanto, Teguh; Marlina, Lina (Lampung University, 2021)
This research aims to analyze the income and welfare levels of of pepper farmers in Melinting Sub- District, East Lampung Regency. The location of the research is chosen purposively. The number of respondents in this reasearch is 43 farmers who are selected using simple random sampling. The methods of analysis used in this research are quantitative method to calculate household income and descriptive qualitative method to determine welfare levels. The results of this research showed that the total income of pepper farming is included in the low category which is IDR1,691,026.16 per month with the contribution of 25.63% towards household income. Based on the criteria of Badan Pusat Statistik in 2014, 100% of pepper farmer households are in the prosperous category, while 20.93% included in the high welfare category based on the subjective welfare indicators.Key words: household, income, pepper, welfare.